First In Silico Study of Two Echinococcus granulosus Glyceraldehyde-3-Phosphate Dehydrogenase Isoenzymes Recognized by Liver Cystic Echinococcosis Human Sera - Agüero, Facundo Ariel (2025)
Cystic echinococcosis (CE) is an endemic zoonotic disease caused by Echinococcus granulosus, which forms cysts in ungulates’ intermediate hosts. Humans are accidental hosts, and CE affects more than one million people worldwide. Imaging remains the diagnostic gold standard, outperforming serological methods. This study presents an in silico analysis of two glyceraldehyde-3-phosphate dehydrogenase (GAPDH) isoenzymes from E. granulosus (EgGAPDH), isolated from a parasite cell line (EGPE). EgGAPDHs were recognized by sera from CE patients, identified through LC-MS/MS and PCR of metacestodes from cattle liver. One isoenzyme is intracellular (IC) (UniProt: W6UJ19), and the other is extracellular (EC) (UniProt: W6V1T8). GAPDH is involved in host–parasite interactions and metabolic processes. We characterized the physicochemical properties; linear epitopes (LEPs); and amino acid domains of EgGAPDH, its hosts, and other parasites. W6UJ19 emerged as the most promising isoenzyme as a marker of infection. Molecular dynamics simulations of isoenzymes, performed in the presence or absence of two bisphosphonates (BPs), revealed how drug binding alters conformational epitopes (CEPs) and suggested that W6UJ19 is more responsive to BP modulation. Binding affinity analysis using the MMPBSA method revealed that etidronate (EHDP) binds EgGAPDH with greater affinity than phosphate (Pi) and alendronate (AL), in the following order: EHDP > Pi > AL.